The position of entry point in total knee arthroplasty is associate with femoral bowing both in coronal and sagittal planes - Zeng, Xianli; Yang, Yiming; Jia, Zhenyu; Chen, Jiarong; Shen, Hongyuan; Jin, Yan; Lu, Yao; Li, Pingyue (Frontiers in Surgery, 2022)
Objective: To investigate the femoral entry point of the intramedullary (IM) guiding rod applied to total knee arthroplasty (TKA) in Chinese subjects and the relationship with femoral bowing in the coronal and sagittal planes through three-dimensional (3D) validation methods. Methods: Computed tomography (CT) images of 80 femurs in Chinese subjects were imported into Mimics 19.0 to construct 3D models. All operations were conducted by Rhinoceros software 5.0. The position of the IM rod entry point was assessed by calculating the distance between the entry point and the apex of the intercondylar notch (AIN) in the coronal and sagittal planes. The coronal femoral bowing angle (cFBA) and sagittal femoral bowing angle (sFBA) were also measured. Results: The average optimal entry point was 0.17 mm medial and 12.37 mm anterior to the AIN in males, while it was 0.02 mm lateral and 16.13 mm anterior to the AIN in females. There was a significant difference between males and females in the sagittal plane (t=-6.570, p=0.000). The mean cFBA was 1.68 ± 2.29°, and the mean sFBA was 12.66 ± 1.98°. The sFBA was strongly correlated with the anterior distance of the proper entry point, and the cFBA was moderately correlated with the lateral distance of the proper entry point. Conclusions: There was a strong correlation between the position of the entry point and the femoral bowing angle in both the coronal and sagittal planes. Thus, to achieve better alignment, the position of the entry point should be measured individually based on femoral bowing.